Improving survival among Brazilian children with perinatally-acquired AIDS. - Matida, Luiza Harunari; Marcopito, Luiz Francisco; Succi, Regina Celia de Menezes; Marques, Heloisa Helena de Souza; Della Negra, Marinella; Grangeiro, Alexandre; Hearst, Norman (FapUNIFESP (SciELO), 2004)
Brazil was the first developing country to provide free, universal access to antiretroviral treatment for AIDS patients. The Brazilian experience thus provides the first evidence regarding the impact of such treatment on the survival of perinatally acquired AIDS cases in the developing world. MATERIAL AND METHODS: This retrospective cohort study used medical record reviews to examine characteristics and trends in the survival of a representative sample of 914 perinatally acquired AIDS cases in 10 Brazilian cities diagnosed between 1983 and 1998. RESULTS: Survival time increased steadily and substantially. Whereas half of the children died within 20 months of diagnosis at the beginning of the epidemic, 75% of children diagnosed in 1997 and 1998 were still alive after four years of follow-up. CONCLUSIONS: Advances in management and treatment have made a great difference in the survival of Brazilian children with AIDS. These results argue strongly for making such treatment available to children in the entire developing world.